Salinity in Autumn-Winter Season and Fruit Quality of Tomato Landraces - Moles, Tommaso Michele; de Brito Francisco, Rita; Mariotti, Lorenzo; Pompeiano, Antonio; Lupini, Antonio; Incrocci, Luca; Carmassi, Giulia; Scartazza, Andrea; Pistelli, Laura; Guglielminetti, Lorenzo; Pardossi, Alberto; Sunseri, Francesco; et al. (Frontiers in Plant Science, 2019)
Tomato landraces, originated by adaptive responses to local habitats, are considered a valuable resource for many traits of agronomic interest, including fruit nutritional quality. Primary and secondary metabolites are essential determinants of fruit organoleptic quality, and some of them, such as carotenoids and phenolics, have been associated with beneficial proprieties for human health. Landraces’ fruit taste and flavour are often preferred by consumers compared to the commercial varieties’ ones. In an autumn-winter greenhouse hydroponic experiment, the response of three Southern-Italy tomato landraces (Ciettaicale, Linosa and Corleone) and one commercial cultivar (UC-82B) to different concentrations of sodium chloride (0 mM, 60 mM or 120 mM NaCl) were evaluated. At harvest, no losses in marketable yield were noticed in any of the tested genotypes. However, under salt stress, fresh fruit yield as well as fruit calcium concentration were higher affected in the commercial cultivar than in the landraces. Furthermore, UC-82B showed a trend of decreasing lycopene and total antioxidant capacity with increasing salt concentration, whereas no changes in these parameters were observed in the landraces under 60 mM NaCl. Landraces under 120 mM NaCl accumulated more fructose and glucose in the fruits, while salt did not affect hexoses levels in UC-82B. UHPLC-MS analysis revealed differential accumulation of glycoalkaloids, phenolic acids, flavonoids and their derivatives in the landrace fruits under stress in all genotypes. Overall, the investigated Italian landraces showed a different behaviour compared to the commercial variety UC-82B under moderate salinity stress, showing a tolerable compromise between yield and quality attributes. Our results point to the feasible use of tomato landraces as a target to select interesting genetic traits to improve fruit quality under stress conditions.